Empowering Youth Health Cadres as an Effort to Prevent Diabetes Mellitus among Adolescents in Banyumanik Village, Semarang City - Golo, Zefan Adiputra; Masrochah, Siti; Fahyudi, Asharul (Jurnal Pengabdian Masyarakat Lentora, 2025)
The incidence of Diabetes Mellitus (DM) among adolescents in Semarang City increased from 242 cases in 2021 to 344 in 2022, highlighting a pressing need for effective preventive interventions. Peer education through Youth Health Cadres (KKR) is a promising strategy to address this issue. This community service program aimed to evaluate the impact of an educational intervention on DM-related knowledge among prospective KKRs at SMPN 12 Banyumanik. The program involved 20 students and was conducted through a single session comprising a pre-test, an interactive educational module on DM etiology and prevention, practical training, and a post-test. Knowledge was measured using a validated 20-item questionnaire. The results demonstrated the proportion of students achieving a 'good' knowledge level increased from 15% to 85%. In conclusion, the targeted educational intervention successfully enhanced the knowledge of Youth Health Cadres. This empowerment provides a critical foundation for their role as agents of change in disseminating DM prevention information within their school environment, contributing to broader public health efforts against the disease.